PENGARUH PERSEPSI KONSUMEN MENGENAI ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN BUAH ALPUKAT MENTEGA SECARA ONLINE (Suatu Kasus Pada Konsumen Kojama Shop) - Belva Ilaika Rahmadini Girawan; Pandi Pardian; Agriani Hermita Sadeli; Dika Supyandi (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Currently, agricultural products, especially fruit, tend to be enjoyed fresh and a variety of processed products is quite rare, especially in avocados. Now the sale of fresh fruit including avocado is not only available in traditional markets or modern markets but also available in online stores. One of the business players who use social media as a platform for selling fruit is the Kojama Shop. The purpose of this study was to determine the characteristics of avocado butter consumers at the Kojama Shop and to analyze the influence of consumers on product attributes on purchasing decisions for avocado butter online at the Kojama Shop. The sampling technique used in this study was non-probability sampling, namely convenience sampling or accidental sampling with the criteria that the person was an avocado consumer at Kojama Shop. The research method used is multiple linear regression analysis to determine whether each perception has a significant effect on purchases. The results of the F test showed that the variables of quality, price, and brand image simultaneously had a positive effect on the purchase decision of avocado butter at the Kojama Shop. The results of the t test showed that each variable of product quality (0.002), product price (0.002), and brand image (0.000) had a significant and significant effect on the purchase decision of avocado butter at Kojama Shop.